The analgesic and acute anti-inflammatory effect of the ethanolic extract of the leaves of Paederia foetida (EEPF) on experimental animal models (Bangladesh Journal of Medical Science, 2012)
Objective:To study the analgesic and acute anti-inflammatory effect of the ethanolic extract of the leaves of Paederia foetida (EEPF) on experimental animal models. Materials and Methods: Fresh leaves were collected, air-dried, powdered, and percolated in 95% ethanol. Acute toxicity test was done according to OECD guidelines. Healthy albino rats (150-200 gm) of either sex were taken and divided into five groups with six animals in each group for central analgesic activity by tail flick method. Peripheral analgesic activity by 1% glacial acetic acid induced writhing test by taking albino mice (20-30 gm) of either sex which were divided into three groups with six animals in each. EEPF was used in a dose of 500 mg/kg bodyweight subcutaneously for tail-flick method and orally for writhing test. In tail-flick method the basal reaction time was taken and a cut-off period of 10 sec was observed. Reaction time were recorded at predrug, 15, 30, 60, 90, 120, 150 and 180 minutes after administration of drug . The standard drug used for central analgesic activity was pethidine 5 mg/kg bw, naloxone 1mg/kg as antagonist and naloxone 1mg/kg bw with 500mg/kg bw of EEPF to study the central mechanism of action. The standard drug used for peripheral analgesic activity was aspirin 100mg/kg bw orally. A control group was maintained in all the models. For anti-inflammatory study, three groups of animals of either sex (n = 6), weighing 150-200g of the species Rattus norvegicus were taken for the study. Group A was taken as control (Normal salie, 10 mL/kg body weight), Group B as test group (EEPF 500 mg/kg body weight), and Group C as standard (Aspirin 100 mg/kg body weight). The animals were studied for acute inflammation by Carrageenan-induced rat paw edema. Statistical analysis  was done by one-way analysis of variance followed by multiple comparison tests.Results: EEPF significantly increased the reaction time in tail-flick method (p